A General Algorithm and Sensitivity Analysis for Variational Inequalities (Journal of Computational Mathematics, 2018)
The fixed point technique is used to prove the existence of a solution for a class of variational inequalities related with odd order boundary value problems and to suggest a general algorithm. We also make the sensitivity analysis for these variational inequalities and complementarity problems using the projection technique. Several special cases are discussed, which can be obtained from our results.